Le développement de la compétence argumentative et l'initiation au discours académique - Górecka, Joanna (Wydawnictwo Naukowe UAM, 2007)
The aim of the paper is to present the specificity of oral argumentative competence in a foreign language and to propose a tentative model of task-based learning of argumentative discourse. It is assumed in the paper that the communicative situation tasks proposed during classes of French as a foreign language in the French Philology Department should contribute to the academic discourse learning. In the paper we present an analysis of two fragments of argumentative situations; the first one concerns the so-called everyday argumentative situation and another one illustrates an argumentative orientation of academic discourse.
The development of argumentative competence and introduction to academic discourse
Keywords: argumentative competence; foreign language; argumentative discourse; French language